2021
DOI: 10.1021/acs.jnatprod.0c01003
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Doscadenamides Activate Quorum Sensing in Gram-Negative Bacteria and Synergize with TRAIL to Induce Apoptosis in Cancer Cells

Abstract: New cyanobacteria-derived bifunctional analogues of doscadenamide A, a LasR-dependent quorum sensing (QS) activator in Pseudomonas aeruginosa, characterized by dual acylation of the pyrrolinone core structure and the pendant side chain primary amine to form an imide/amide hybrid are reported. The identities of doscadenamides B−J were confirmed through total synthesis and a strategic focused library with different acylation and unsaturation patterns was created. Key molecular interactions for binding with LasR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This molecule was not able to be isolated in pure form in sufficient quantity for empirical structural characterization in this study, and is suggested for targeted isolation, structure elucidation, and more accurate pharmacological characterization in future research. This strategy of structure proposal based on MS/MS fragmentation analysis and molecular networking for compounds beyond isolation in the initial study, later followed by targeted isolation or synthesis for confirmation and structure-activity relationship (SAR) study, has been recently exemplified by Gerwick, Luesch, and coworkers in the expansion of the cyanobacterial natural product family of doscadenamides [ 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…This molecule was not able to be isolated in pure form in sufficient quantity for empirical structural characterization in this study, and is suggested for targeted isolation, structure elucidation, and more accurate pharmacological characterization in future research. This strategy of structure proposal based on MS/MS fragmentation analysis and molecular networking for compounds beyond isolation in the initial study, later followed by targeted isolation or synthesis for confirmation and structure-activity relationship (SAR) study, has been recently exemplified by Gerwick, Luesch, and coworkers in the expansion of the cyanobacterial natural product family of doscadenamides [ 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, pterostilbene (PTER), a natural analogue of resveratrol, was proved to enhance TRAIL-induced apoptosis via reactive oxygen species (ROS)-mediated C/EBP homologous protein (CHOP) activation, leading to the expression of DR4 and DR5 [ 34 ]. Like PTER, doscadenamide A could also synergistically interact with TRAIL that induced exogenous apoptosis, and bound to death receptors to induce apoptosis of TNBC cells [ 35 ].…”
Section: Targeting Apoptotic Pathways With Small-molecule Compounds I...mentioning
confidence: 99%